Students’ Misconceptions on the Dynamic Equilibrium - Utami, Dita Putri; Salirawati, Das (Jurnal Pendidikan: Teori, Penelitian, dan Pengembangan, 2023)
This study aims to describe students' misconceptions in dynamic equilibrium. Descriptive analysis was employed. The sample was 164 students from three high schools with different categories. Data is collected by test and interview. The test is a Two-tier multiple-choice test with a reliability of 0.71. Test results show the misconception in each school is still relatively high. Interviews results show that students’ think the reactions involving substances in solid and liquid cannot reach equilibrium. They also have the perception that the equilibrium reaction only occurs if the coefficient of the substance on the left and the right are same.